Tuning the optical properties of Ln3+-doped-Y2O3@ZnO@Au core-shell heterostructures for visible-to-NIR photon harvesting - Jayswal, Shefali; Luwang, Meitram Niraj; Moirangthem, Rakesh S. (Surfaces and Interfaces, 2024)
Here, compact Yb3+-Er3+-Tm3+ doped Y2O3 phosphor microspheres were synthesized by solvothermal method which gave emission in the entire visible region under 980 nm excitation. The effect of doping alkali ions like lithium on the upconversion emission of YYET phosphors is investigated. An epitaxial layer of ZnO is grown around the YYETL (Li+ doped YYET) microspheres by hydrothermal technique. An analysis of the influence of the ZnO shell thickness on the upconversion emission of core microspheres is done. Initial growth of a thin layer of ZnO on the YYETL microspheres causes enhancement in upconversion emission due to passivation of surface defects of core microspheres. Quenching of anti-Stokes emission occurs for thicker ZnO shell coating. Further, it is decorated with AuNPs to study the effect of plasmonics on the optical property of the developed heterostructure. The overlap between the upconversion emission spectra of core microspheres and the LSPR peak of AuNPs modulates the property of the entire structure. The optimized samples were checked for photocatalytic application by degradation of Rh6G dye under solar irradiation. YYETL@ZnO@Au core-shell samples exhibited highest rate constant of 0.00395 min(-1), which is attributed to better exploitation of the UV-Vis-NIR region of the solar spectrum by all three components of the heterostructure.
Keywords: AuNPs; Core-shell heterostructure; LRET; Photocatalysis; Upconversion microspheres; ZnO